Perception of Students and Faculty on Problem Based Learning in Proficiency Certificate Level Nursing Program - Maharjan, Babu Raja; Shrestha, Uttam; Shrestha, Ashis; Acharya, Balakrishnan M; Poudel, Ambika; KC, Sarala; Gongal, Rajesh N (Journal of Nepal Health Research Council, 2021)
Background: Patan Academy of Health Sciences intended to implement problem based learning in proficiency certificate level nursing program who have just completed grade 10. Presently in Nepal, the available literature on use of problem based learning as teaching learning methods is limited to undergraduate medicine who have passed 10+2 or equivalent. It was conducted to measure the perception of students and faculty on problem based learning in nursing program. Methods: Nursing faculty who have been involved in teaching learning of nursing curriculum were trained to conduct problem based learning and write problem based learning case. Prior to run problem based learning case, students were also oriented for the problem based learning process. A 44 students and seven faculty returned the filled data collection tool. Results: Both the students and tutors perceived that the problem based learning is an effective teaching learning method. They also found that the attributes of problem based learning such as self-directed learning, collaborative learning, team work and fun learning. Students were eager to have more problem based learning session in their curriculum. Faculty also perceived that problem based learning can be a better teaching learning methods and it can be implemented in proficiency certificate level nursing. Conclusions: This study shows the acceptance of problem based learning as a teaching learning methods in proficiency certificate level nursing program by both the students and faculty. Keywords: Nursing curriculum; PBL; perception.